The relationship between service quality, customer satisfaction and customer loyalty in the retail supermarket industry - Ndhlovu, Thinkwell (Rhodes University, Faculty of Commerce, Department of Management, 2014)
The increasingly competitive business environment has influenced contemporary organisations to build mutual beneficial relationships with their customers indicating a paradigm shift from transactional marketing. In order to compete in this intense competitive environment, organisations are creating competitive advantage over their rivals through service quality that will influence customer satisfaction which subsequently leads to customer loyalty. Service quality has been found to be the key strategy of success and survival for most organisations like retail supermarkets who want to win the loyalty of their customers because of its positive effect on customer satisfaction. The purpose of this research was to determine the relationship between service quality, customer satisfaction and customer loyalty in the retail supermarket industry. An empirical study was conducted in Grahamstown between two main supermarkets through a survey that determined customers' perceptions on service quality, customer satisfaction and customer loyalty respectively. The empirical findings of this research study revealed that moderate to strong positive linear relationships exists between the dimensions of service quality (namely physical aspects, reliability, personal interaction, problem solving and policy) and customer satisfaction at the 5% level of significance. Furthermore, this study showed that dimensions of service quality (namely physical aspects, reliability, personal interaction and problem solving) have weak negative linear relationships with price sensitivity dimension of customer loyalty. The study further showed that the dimensions of service quality (namely physical aspects, reliability, personal interaction, problem solving and policy) have weak to moderate positive linear relationships with the purchase intentions dimension of customer loyalty. In addition, all the dimensions of service quality (namely physical aspects, reliability, personal interaction, problem solving and policy) showed moderate positive linear relationships with word of mouth communication dimension of customer loyalty. A weak negative linear relationship between price sensitivity dimension of customer loyalty and customer satisfaction was revealed in this study. Purchase intentions dimension of customer loyalty was also found to have a moderate positive linear relationship with customer satisfaction. In addition, word of mouth communication dimension of customer loyalty showed a strong positive linear relationship with customer satisfaction. There is sufficient evidence that the customers of the two supermarkets in this study have different perceptions on problem solving dimension of service quality. This study further provides sufficient evidence of the significant difference between gender on the levels of customer satisfaction. In addition, this study showed that customers of various levels of education and occupations differ in price sensitivity dimension of customer loyalty. The average scores for word of mouth communication, purchase intentions and price sensitivity dimensions of customer loyalty were found to be significantly different between the two supermarkets investigated in this study. Therefore, for supermarkets to compete effectively in the intense retail supermarket industry in South Africa they have to manage their service quality dimensions so as to influence customer satisfaction and customer loyalty respectively.
Keywords: Consumer satisfaction; Customer loyalty; Customer services -- Rating of; Customer services -- Quality control; Relationship marketing; Supermarkets -- South Africa -- Grahamstown